Peran Religiusitas dalam Membangun Motivasi pada Generasi Z - Elza Sabillah (UIN Sunan Gunung Djati Bandung, 2023)
Religiosity is a human belief in something. Religiosity regulates all aspects of human life. One of them is how humans explore their potential and actualize it so as to achieve a personal branding. The two potentials that exist in humans are good and bad. This good potential raises motivation to be achieved in the corridors of goodness that have been regulated by religion. This study aims to discuss the role of religion in building motivation in Gen Z. This research also uses a qualitative approach by applying a descriptive-analytical method. Data collection techniques were carried out through library research. Data analysis techniques are taken through the stages of inventory, classification, and interpretation. So that we get a meeting point that there is a religious role in building the motivation of generation Z where religiosity directs more how to reach the potential with the potential for goodness that is possessed. To achieve this potential must be driven by motivation. because meeting the needs and self-actualization need motivation.